1991
DOI: 10.1002/ana.410300203
|View full text |Cite
|
Sign up to set email alerts
|

Ocular motor abnormalities in human immunodeficiency virus infection

Abstract: We studied ocular motor performance in 47 subjects with human immunodeficiency virus (HIV) infection and 25 normal control subjects. Saccade accuracy was the most sensitive measure, being significantly poorer for all four HIV-positive groups (asymptomatic, acquired immunodeficiency syndrome [AIDS] without dementia, and AIDS with dementia, and AIDS-related complex) than for control subjects. While saccade duration and peak velocity were not significantly different across groups, the scatter of saccade duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Eye movement abnormalities are common. These ocular motility disorders include slowed saccadic eye movements (252,268,315), hypometric saccades (76), overshoot dysmetria (114), fixational instability (76), and defective smooth pursuits (76). Currie and colleagues found these eye movement abnormalities useful predictive markers for the development of HIV-1 encephalopathy (76).…”
Section: Hiv-1 Encephalopathy (Hiv-1-associatedmentioning
confidence: 99%
“…Eye movement abnormalities are common. These ocular motility disorders include slowed saccadic eye movements (252,268,315), hypometric saccades (76), overshoot dysmetria (114), fixational instability (76), and defective smooth pursuits (76). Currie and colleagues found these eye movement abnormalities useful predictive markers for the development of HIV-1 encephalopathy (76).…”
Section: Hiv-1 Encephalopathy (Hiv-1-associatedmentioning
confidence: 99%
“…This finding is consistent with the result of previous clinical and electrophysiological studies, which have shown that abnormal saccades and smooth pursuits are present in HIV infected subjects including those without any other clinical manifestation of HIV infection. [23][24][25][26][27] These ocular movement disturbances are believed to be more frequent in subjects with HIV dementia. Some investigators have postulated that in asymptomatic HIV subjects they represent early manifestations of HIV dementia.…”
Section: Discussionmentioning
confidence: 99%
“…153,154 Saccadic problems in HIV positive patients include hypometric saccades, anticipatory saccades, wrong way saccades, abnormal antisaccades, fixation instability with saccadic intrusions and square wave jerks, slowed saccadic duration both for abducting and adducting saccades, and reduced saccadic velocity. [153][154][155][156] Smooth pursuit dysfunction includes saccadic pursuit and decreased smooth pursuit gain.…”
Section: Supranuclear Defectsmentioning
confidence: 99%
“…Abnormal saccades and smooth pursuit may be an early indicator of AIDS dementia complex (ADC) 153,155,157 characterized by progressive cognitive loss with behavioral problems and slowing of rapid motor movements. These ocular motility problems may be encountered even in patients without signs of ADC.…”
Section: Supranuclear Defectsmentioning
confidence: 99%